If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 60 = 40 + 2w Solving 60 = 40 + 2w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-2w' to each side of the equation. 60 + -2w = 40 + 2w + -2w Combine like terms: 2w + -2w = 0 60 + -2w = 40 + 0 60 + -2w = 40 Add '-60' to each side of the equation. 60 + -60 + -2w = 40 + -60 Combine like terms: 60 + -60 = 0 0 + -2w = 40 + -60 -2w = 40 + -60 Combine like terms: 40 + -60 = -20 -2w = -20 Divide each side by '-2'. w = 10 Simplifying w = 10
| (32X^-10*Y^4/7)^3/5 | | 9x+9x=4 | | 3-4(x+6)=3 | | (8m+5)(8m-5)=0 | | 7+10s+-1s+1s= | | -82-5x=3x+54 | | 7+7t-4+-6= | | -48-5x=12-7x | | 10-4yi=2x+24i | | 2(-2+x)=x-.875 | | 72/10,000 | | 10(10+c)+2=10 | | 10(10+c)+2=100 | | -14+12x=12+10x | | -5u+14=4u+32 | | 1.5d+3.25=1+2.25s | | 100(10+c)+0=10 | | xsquared-9x=-8 | | 1/3m=33 | | -3u+15=9u-45 | | 6x-30=x+16 | | -83-2x=-10x+93 | | x-1=-2/4x-1/4 | | 4X+17+28=6X | | 5/9=b-1/3 | | 1+5p=11+3p | | -56+3x=5x+80 | | 4(7y-6)-(9y+9)= | | 8(12+9)= | | 6m+2=8 | | a+(-11)=-13 | | 7x+10=210 |